2002
DOI: 10.1016/s0006-3495(02)75444-1
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium Phenomena in the Phase Separation of a Two-Component Lipid Bilayer

Abstract: Lipid bilayers composed of two phospholipids with significant acyl-chain mismatch behave as nonideal mixtures. Although many of these systems are well characterized from the equilibrium point of view, studies concerning their nonequilibrium dynamics are still rare. The kinetics of lipid demixing (phase separation) was studied in model membranes (large unilamellar vesicles of 1:1 dilauroylphosphatidylcholine (C(12) acyl chain) and distearoylphosphatidylcholine (C(18) acyl chain)). For this purpose, photophysica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 47 publications
6
71
0
Order By: Relevance
“…As shown, changes in the energy transfer efficiency for ShB are in full agreement with the theoretical expectation for membrane bidimensional random distribution of donors and acceptors within the same plane (37). The acceptor (t-PnA) is known to be internalized in the membrane (38), and from molecular models a distance of about 12.1 Å to the aqueous interface has been estimated (39). In this way, it can be concluded that tyrosine in ShB is located into the membrane at this depth.…”
Section: R(t) ) R′(t)esupporting
confidence: 83%
“…As shown, changes in the energy transfer efficiency for ShB are in full agreement with the theoretical expectation for membrane bidimensional random distribution of donors and acceptors within the same plane (37). The acceptor (t-PnA) is known to be internalized in the membrane (38), and from molecular models a distance of about 12.1 Å to the aqueous interface has been estimated (39). In this way, it can be concluded that tyrosine in ShB is located into the membrane at this depth.…”
Section: R(t) ) R′(t)esupporting
confidence: 83%
“…The thickness of the lipid film was estimated as reported in the literature [5,27] fixing the real part of the refractive index at 1.5 [29,30]. The very low extinction coefficient values (k) obtained in this work ranged from 0.03 to 0.11, which indicates nearly transparent films, as expected for thin organic layers [27].…”
Section: Ellipsometrysupporting
confidence: 60%
“…[17][18][19] Used as FRET donors, NBD-diC n PE probes form, together with acceptor rhodamine B PE derivatives, a very well-known Förster pair for the studies of membrane organization [20][21][22][23][24] as well as quantification of lipid mixing and exchange. 25 Alternatively, NBD probes can be used as acceptors to chromophores including diphenylhexatriene 26,27 or trans-parinaric acid, 28 or even as donors and acceptors simultaneously in homo-FRET studies. 20 Several fluorescence spectroscopic and microscopic studies have also indicated that, contrary to the vast majority of membrane fluorescent probes, doubly saturated long-chained NBD-diC n PE partitions favourably to liquid ordered (lo) phases in systems displaying lo/liquid disordered phase coexistence, 22,24,29,30 although the phase preference depends both on the probe acyl chain length and the composition of the underlying lipid mixture.…”
Section: Introductionmentioning
confidence: 99%